(untitled) (Journal of Nonlinear Modeling and Analysis, 2025)
In this article, the fixed point of the SM iterative approach is approximated via Suzuki mapping. In the context of Banach spaces, we provide both weak and strong convergence for the SM iteration. Then, by comparing it with certain well-known iterations, we give some numerical examples to show the effectiveness of SM iteration for the Suzuki-type mapping.